Quality in Canadian and Swedish Adult Education Policy - Johanna Mufic (Adult Education Research Conference, 2022)
The aim of this paper is to compare and critically scrutinize how quality is construed in Canadian and Swedish adult education policy. The empirical data consists of policy documents and interviews conducted with adult educators.
Keywords: Adult Education; Canada; Comparative study; Sweden; Quality